The Mobile App to Assist with Tattoo-encoded Baby Immunization Records in Africa - Bongkeum JEONG; Jesús IBÁÑEZ; Nuno NUNES; Monchu CHEN (International Journal of Applied Methods in Electronics and Computers, 2018)
This paper describes the design and implementation of a mobile application that assists with the interpretation and generation of tattoos which encode immunization records. That explains the application of ethnography design, in a broad way, to solve the issues of the vaccination system for children in Africa. We have derived the “tattoo of Africa” concept from a design that reflects African cultural backgrounds and have linked it with the health service design process. Tattoos, which have been common in Africa for thousands of years, have been redefined as a new ritual for child health records. Our design is applied to two different artefacts: a baby guide book and a baby bracelet. We also describe our first prototype of the baby bracelet and its related App. The bracelet, which contains an NFC tag with information about the baby’s vaccinations, can be read from or written to any NFC-enabled Android smartphone via the visual interface of the related App.